Physiological mechanisms contributing to increased water-use efficiency in winter wheat under organic fertilization. - Linlin Wang; Shiwen Wang; Wei Chen; Hongbing Li; Xiping Deng (PLoS ONE)
Improving the efficiency of resource utilization has received increasing research attention in recent years. In this study, we explored the potential physiological mechanisms underlying improved grain yield and water-use efficiency of winter wheat (Triticum aestivum L.) following organic fertilizer application. Two wheat cultivars, ChangHan58 (CH58) and XiNong9871 (XN9871), were grown under the same nitrogen (N) fertilizer rate (urea-N, CK; and manure plus urea-N, M) and under two watering regimes (WW, well-watered; and WS, water stress) imposed after anthesis. The M fertilizer treatment had a higher Pn and lower gs and Tr than CK under both water conditions, in particular, it significantly increased WRC and Ψw, and decreased EWLR and MDA under WS. Also, the M treatment increased post-anthesis N uptake by 81.4 and 16.4% under WS and WW, thus increasing post-anthesis photosynthetic capacity and delaying leaf senescence. Consequently, the M treatment increased post-anthesis DM accumulation under WS and WW by 51.5 and 29.6%, WUEB by 44.5 and 50.9%, grain number per plant by 11.5 and 12.2% and 1000-grain weight by 7.3 and 3.6%, respectively, compared with CK. The grain yield under M treatment increased by 23 and 15%, and water use efficiency (WUEg) by 25 and 23%, respectively. The increased WUE under organic fertilizer treatment was due to elevated photosynthesis and decreased Tr and gs. Our results suggest that the organic fertilizer treatment enabled plants to use water more efficiently under drought stress.